Endotoxin signaling in human macrophages: signaling via an alternate mechanism. - Sacre, S; Andreakos, E; Feldmann, M; Foxwell, B (2004)
Lipopolysaccharide (LPS) signals through Toll-like receptors (TLRs) in the course of sepsis, resulting in the release of inflammatory factors. In cell lines and murine models, parts of the signaling pathways involved have been elucidated with MyD88, Mal/TIRAP and IKK2 playing an important role in the induction of NF-kappaB. By focusing on primary human cells, we have shown that there are fundamental signaling differences between human and murine macrophages and between cells of myeloid and non-myeloid origins. In primary human cells, there are no available knockouts so we employed the use of dominant negatives to investigate the signaling cascades. We show that in primary human macrophages MyD88, Mal/TIRAP and IKK2-independent alternative pathways activate NF-kappaB and induce the expression of inflammatory cytokines, whereas in non-myeloid synovial fibroblasts MyD88 and/or Mal/TIRAP are essential adaptors for LPS signaling.